2011
DOI: 10.2306/scienceasia1513-1874.2011.37.024
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:To examine the effect of selenium (Se) supplementation on shrimp growth and disease resistance after Taura Syndrome virus (TSV) challenge, groups of Pacific white shrimp (Penaeus vannamei) from a strain known to be susceptible to TSV were fed 3 diets: (1) standard commercial shrimp feed (0.58 ppm Se content) without Se supplementation (standard diet group); (2) standard commercial feed plus 0.3 ppm inorganic Se (Inorg Se-group); and (3) standard commercial feed plus 0.3 ppm organic Se (Org Se-group) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…It provides protection to the cells against oxidant materials by increasing the production of selenoenzymes and selenoproteins (GPx system, thioredoxin reductase (TrxR), selenoprotein P, etc.). Thus, an increased amount of these proteins will show a more protective role and thus enhances the immunity status of fish and other animals (Burk et al, 2003;Kumar et al, 2008), while low concentrations of selenoproteins increase oxidative stress, which then leads to viral infection (Sritunyalucksana et al, 2011). These selenoproteins participate actively in the antioxidant defense system and prevent the harmful effects of reactive oxygen species (Tapiero et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It provides protection to the cells against oxidant materials by increasing the production of selenoenzymes and selenoproteins (GPx system, thioredoxin reductase (TrxR), selenoprotein P, etc.). Thus, an increased amount of these proteins will show a more protective role and thus enhances the immunity status of fish and other animals (Burk et al, 2003;Kumar et al, 2008), while low concentrations of selenoproteins increase oxidative stress, which then leads to viral infection (Sritunyalucksana et al, 2011). These selenoproteins participate actively in the antioxidant defense system and prevent the harmful effects of reactive oxygen species (Tapiero et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The practical impact of improved Se status on growth and health has been illustrated in a recent work by Sritunyalucksana, Intaraprasong, Sa‐Nguanrat, Filer and Fegan (2008) with Pacific white shrimp ( Penaeus vannamei ), which demonstrated that the addition of organic selenium to the diet resulted in better growth (Fig. 6).…”
Section: Increasing the Selenium Status Of Farmed Aqua Species: Respomentioning
confidence: 95%
“…On the other hand, in hybrid tilapia, hematocrit level dropped significantly low when selenium supplementation level decreased up to zero levels [24]. Amounts of RBCs, hematocrit, lipids, hemoglobin, glucose and protein increased when the concentration of organic selenium increased in fish feed up to 0.3g/kg clearly indicating the improvement in fish health [25] because of selenium dose. Hematological variables are affected by different protein levels, the weight of fish and related indices [26] as well as due to deficiency of micronutrients like selenium.…”
Section: Introductionmentioning
confidence: 95%